Sosialisasi dan Layanan Servis Sepeda Motor Gratis di Kelurahan Warungboto, Kemantren Umbulharjo, Kota Yogyakarta - Muhammad Arief Saputro; Joko Winarno; Sukamto; Mochamad Syamsiro; Ardiyan Rhamadhani; Riki Ferdiansyah; Sahat Yansen Parulian Sinamo (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
This community service program is an annual activity organized by the Department of Mechanical Engineering, Faculty of Engineering, Janabadra University, focusing on the provision of free motorcycle maintenance services accompanied by public education regarding routine vehicle care for residents living in and around Kalurahan Warungboto. The program aims to enhance the safety and reliability of local residents’ daily transportation through preventive maintenance and increased user technical literacy. The implementation methods include: (1) on-site registration of motorcycles at the Kalurahan Warungboto office, (2) initial inspection using a standardized checklist, (3) basic servicing such as oil changes, air filter cleaning, etc, and (4) brief socialization sessions on maintenance schedules, early signs of malfunction, and safe riding behaviors. The free service is carried out by lecturers and Mechanical Engineering students in the yard of the Kalurahan Warungboto office, allowing residents to easily access the service location and obtain direct consultation on the condition of their motorcycles. While participants wait, the team delivers structured educational materials to support independent vehicle care at home. Expected outcomes include improved functional condition of participant vehicles, increased public understanding of preventive maintenance, and strengthened achievement of student learning outcomes in both technical skills and service-oriented soft skills. The program’s implications include strengthened campus–community networks in Kalurahan Warungboto and the potential replication of the service model in other regions with support from local stakeholders. The community service program is an annual activity organized by the Department of Mechanical Engineering, Faculty of Engineering, Janabadra University, focusing on the provision of free motorcycle maintenance services accompanied by public education regarding routine vehicle care. The program aims to enhance the safety and reliability of local residents’ daily transportation through preventive maintenance and increased user technical literacy.